VENUS: The Online Game Simulator Using Massively Virtual Clients - Jung, YungWoo; Lim, Bum-Hyun; Sim, Kwang-Hyun; Lee, HunJoo; Park, IlKyu; Chung, JaeYong; Lee, Jihong (Systems Modeling and Simulation: Theory and Applications, 2005)
In this paper, we present an efficient method for simulating massively virtual clients in an online game environment. Massively multiplayer online games and other multi-user based networked applications are becoming more attractive to the gamer players. Such kind of technology has long been researched in the area called Networked Virtual Environments. In the game development process, a set of beta tests is used to ensure the stability of online game servers. A set of testing processes consumes a lot of development resources such as cost, time, and etc. The purpose of the VENUS (Virtual Environment Network User Simulator) system is to provide an automated beta test environment to the game developers to efficiently test the online games to reduce development resources.